PENGARUH INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN - Indriati Sumarni; Meina Wulansari Yusniar; Asrid Juniar (Universitas Lambung Mangkurat, 2014)
This study aims to examine the effect of investment opportunity set to dividend policy. Population are manufacturing companies listed in Indonesian Stock Exchange (BEI) in the period 2010-2011. Sample are 58 companies as a sample research based on tecnique purposive sampling and used method quantitative. Data used in this research is secondary data in the from of financial report, Indonesian Capital Market Directory (ICMD) and other references that support this research. Data analysis tecnique uses the classical assumption test: normaly test, multicollinearity test, autocorrelation test and the test heterokedasticity. Test hypothesis using multiple regression analysis using SPSS 17. The result has shown that: LnMVEBVE has negative significant influence to DPR. LnPER has a positive significant effect to DPR. LnCAPXA has negative and significant to DPR. LnDEPV does not effect to DPR